China's distant‐water fisheries in the 21st century. Issue 3 (23rd March 2013) - Pauly, Daniel; Belhabib, Dyhia; Blomeyer, Roland; Cheung, William W W L; Cisneros‐Montemayor, Andrés M; Copeland, Duncan; Harper, Sarah; Lam, Vicky W Y; Mai, Yining; Le Manach, Frédéric; Österblom, Henrik; Mok, Ka Man; et al.
Abstract We conservatively estimate the distant‐water fleet catch of the People's Republic of China for 2000–2011, using a newly assembled database of reported occurrence of Chinese fishing vessels in various parts of the world and information on the annual catch by vessel type. Given the unreliability of official statistics, uncertainty of results was estimated through a regionally stratified Monte Carlo approach, which documents the presence and number of Chinese vessels in Exclusive Economic Zones and then multiplies these by the expected annual catch per vessel. We find that China, which over‐reports its domestic catch, substantially under‐reports the catch of its distant‐water fleets. This catch, estimated at 4.6 million t year−1 (95% central distribution, 3.4–6.1 million t year−1) from 2000 to 2011 (compared with an average of 368 000 t·year−1 reported by China to FAO), corresponds to an ex‐vessel landed value of 8.93 billion € year−1 (95% central distribution, 6.3–12.3 billion). Chinese distant‐water fleets extract the largest catch in African waters (3.1 million t year−1, 95% central distribution, 2.0–4.4 million t), followed by Asia (1.0 million t year−1, 0.56–1.5 million t), Oceania (198 000 t year−1, 144 000–262 000 t), Central and South America (182 000 t year−1, 94 000–299 000 t) and Antarctica (48 000 t year−1, 8 000–129 000 t). The uncertainty of these estimates is relatively high, but several sources of inaccuracy could not be fully resolved given the constraints inherent in the underlying data and method, which also prevented us from distinguishing between legal and illegal catch.